A comparative study on denitrifying sludge granulation with different electron donors: Sulfide, thiosulfate and organics. (November 2017) - Qian, Jin; Wei, Li; Wu, Yaoguo; Wang, Qilin; Fu, Xiaoying; Zhang, Xiaochao; Chang, Xing; Wang, Lianlian; Pei, Xiangjun
Abstract: A comparative study on denitrifying sludge granulation with different electron donors (sulfide, thiosulfate and organics) was carried out. Longer time was spent on sulfide-denitrifying granular sludge (DGS) cultivation (88 days) than thiosulfate- and organics-DGS cultivations (57 days). All the three DGS were characterized in terms of particle size distribution, sludge settling ability (indicated by sludge volume index and settling velocity), permeability (indicated by fractal dimension) and extracellular polymeric substances (EPS, including polysaccharide and protein) secretion. Sludge productions in the three DGS-reactors were also monitored. The key functional microorganisms in three granular reactors were revealed via high through-put pyrosequencing analysis. Batch tests were performed to measure the denitrification activities of each DGS, including both denitratation (NO3 −  → NO2 − ) and denitritation (NO2 −  → N2 ). We found that thiosulfate-driven denitrifying sludge granulation (TDDSG) should be the most efficient and compact technology for effective BNR in municipal wastewater treatment. The findings of this study suggests the TDDSG could further increase the nitrogen removal potential in an enhanced sulfur cycle-driven bioprocess for co-treatment of wet flue gas desulfurization wastes with fresh sewage depending on three short-cut biological reactions, including: 1) short-cut biological sulfur reduction (SO4 2− /SO3 2−  → S2 O3 2− ); 2) thiosulfate-driven denitritation (S2 O3 2−  + NO2 −  → SO4 2−  + N2 ↑); and 3) nitritation (NH4 +  + O2  → NO2 − ). Graphical abstract: Highlights: Denitrifying granular sludge (DGS) was cultivated with different electron donors. Longer time was required for sulfide-DGS cultivation. Characteristics among sulfide-, thiosulfate- and organics-DGS were compared. S2 O3 2 − -driven denitrifying sludge granulation is the most compact technology for BNR.